2022
DOI: 10.3390/biomedicines10092244
|View full text |Cite
|
Sign up to set email alerts
|

Level of Potassium Is Associated with Saturated Fatty Acids in Cell Membranes and Influences the Activation of the 9 and 13 HODE and 5 HETE Synthesis Pathways in PCOS

Abstract: Potassium helps to maintain the water–electrolyte and acid–base balance. There is little research on the relationship between plasma fatty acids (FAs), inflammatory mediators and red blood cell potassium levels in women with polycystic ovary syndrome (PCOS). This study included 38 Caucasian women with PCOS. Potassium in the erythrocytes was determined by inductively coupled atomic plasma emission spectrometry. The FAs were analysed with gas chromatography, and liquid chromatography was used to separate the eic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has been shown that the concentration of potassium in erythrocytes in women with PCOS is significantly higher than in healthy women [2] showed the existence of significant negative relationships between the amount of potassium in the erythrocytes of women with PCOS and saturated fatty acids in cell membranes. Saturated fatty acids cause a decrease in potassium influx into the cell by destabilizing the pH of the cytosol [35]. Although there is no information on potassium supplementation in women with PCOS, it seems reasonable to introduce this element to the diet, especially in cases where it is necessary to eliminate products with a high glycemic index (bananas, potatoes, sweet potatoes), which are the main source of potassium.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the concentration of potassium in erythrocytes in women with PCOS is significantly higher than in healthy women [2] showed the existence of significant negative relationships between the amount of potassium in the erythrocytes of women with PCOS and saturated fatty acids in cell membranes. Saturated fatty acids cause a decrease in potassium influx into the cell by destabilizing the pH of the cytosol [35]. Although there is no information on potassium supplementation in women with PCOS, it seems reasonable to introduce this element to the diet, especially in cases where it is necessary to eliminate products with a high glycemic index (bananas, potatoes, sweet potatoes), which are the main source of potassium.…”
Section: Resultsmentioning
confidence: 99%
“…PCOS metabolic anomalies are demonstrated to be related to incorrect element metabolism. A clinical study by Szczuko et al [13] examined the degree of dependence between erythrocytes potassium concentration, saturated fatty acids (SFAs) levels, and inflammatory mediators in PCOS women. Although the involved processes warrant further investigations, the authors explain that increased SFAs in red-blood-cell membranes reduced potassium influx by destabilizing the cytosol pH and increasing the inflammatory response through the activation of the AA (arachidonic acid) cascade, in which the 9, 13 HODE (derivatives synthesized from linolenic acid) and 5LOX pathways are mainly involved.…”
mentioning
confidence: 99%